Edukasi Pengenalan Stunting Pada Remaja Putri - Muchtar, Febriana; Rejeki, Sri; Elvira, Ilian; Hastian, Hastian (Universitas Negeri Gorontalo, 2023)
Stunting is a chronic nutritional problem that prevention must be done earliest. Therefore, information about stunting must be given to adolescent girls to prepare them to become prospective mothers with good nutrition and health status. The purpose of the community service is to provide information, knowledge, and understanding to adolescent girls about stunting as one of the nutritional problems in Indonesia. Community service is carried out by counseling with lectures and discussion methods. The school highly appreciates the community service activity. Counseling can increase the knowledge of adolescent girls about stunting. The material about stunting can be understood by adolescent girls marked by appropriate answers to questions during the discussion. Teenage girls are expected to be able to implement behaviors that can improve their health to prevent stunting from an early stage and can disseminate information.